Pengembangan Model Pembelajaran IPA SD Berbasis Bahan Di Lingkungan Sekitar Melalui Pendekatan Starter Eksperimen - Muharram --; Hamka Lodang; Nurhayati --; Munir Tanrere (Jurnal Pendidikan dan Kebudayaan, 2010)
This study is a research and development that was conducted through four steps and is mentioned as a â€œFour-D Modelâ€, namely define, design, develop and disseminate. The aim of this research is to produce instructional model, that is a starter experiment based on environmental materials and supporting of instructional model, including: experiment guidance, student worksheet and instrument ofÂ evaluation. The product of this research is the syntax of instructional model that consist of six steps and supporting of the model, namely three supplement books for Elementary School. The titles of the books are â€œScience Skillâ€ for 4th, 5th, and 6th Gradeâ€. The instructional model and its supporting were validated by expertâ€™s team and they were categorized in valid that are 88.40% for instructional model and 84.66% for the supporting of the instructional model. Try out result that conducted through the pre-experiment results showed that: 1) the instructional model and its supporting could be used by both the teacher and the student; 2) Apply the model and its supporting increase the activity, interest, scientific attitude, skill of science process, and the studentâ€™s achievement.